Herpes Simplex Treated With Antimicrobial Photodynamic Therapy: Randomized Controlled Trial - La Selva, Andreia; Bezerra, Daniella Teixeira; Zerbinati, Rodrigo Melim; Gonçalves, Marcela Leticia Leal; Navarro, Ricardo Scarparo; Bello‐Silva, Marina Stella; Ando‐Suguimoto, Ellen Sayuri; Aranha, Ana Cecília Corrêa; Braz‐Silva, Paulo Henrique; Ramalho, Karen Muller; Motta, Lara Jansiski; Fernandes, Kristianne Porta Santos; et al. (Journal of oral pathology & medicine, 2025)
ABSTRACT Objective To compare the efficacy of antimicrobial photodynamic therapy (aPDT) with topical acyclovir in terms of healing time for herpes simplex lesions, recurrence rates, HSV‐1 quantification in secretion and saliva, pain levels, temperature changes, and outcomes measured by the Oral Health Impact Profile Questionnaire (OHIP‐14). Subjects and Methods Patients with vesicle or ulcer phase lesions were randomly divided into two groups: the control group (topical acyclovir four times daily for 7 days + aPDT simulation, n = 12) and the experimental group (placebo acyclovir ointment + aPDT applied once, n = 12). The primary outcome was lesion resolution time, with secondary assessments for recurrence, pain, local temperature, virus quantification via quantitative polymerase chain reaction (qPCR), and impact on quality of life. Results After 1 year, the remission and recurrence rates were similar between groups (p = 0.718 and p = 0.317, respectively), as were pain levels and temperature (p = 0.039 and 0.217). There was an increase in HSV‐1 viral load in saliva, measured by qPCR, on Day 3 in the ACV group (p = 0.043). The OHIP‐14 scores were similar between groups after 1 year. Conclusion This study found no differences between aPDT and topical acyclovir regarding lesion resolution time, recurrence rates, pain levels, local temperature changes, and OHIP‐14 scores. Both treatments showed similar efficacy in managing herpes simplex lesions over 1 year. While there was an increase in HSV‐1 viral load in saliva in the acyclovir group on Day 3, this did not translate into differences in clinical outcomes between the groups. Trial Registration NCT 04037475